2021
DOI: 10.3390/healthcare9111433
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Fatalities or Severe Injuries to Pedestrians Lying on the Road in Japan: Nationwide Police Database Study

Abstract: To help reduce the number of pedestrians lying on the road suffering fatal or severe injuries as a result of vehicle collisions, we investigated the influencing factors. We conducted an analysis of the records of the Institute for Traffic Accident Research and Data Analysis Japan between 2012 and 2018; we found that 2452 pedestrians lying on the road were involved in collisions (797 fatalities, 784 severely injured, 871 mildly injured). Multivariate logistic regression analysis identified the following as majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…The male preponderance of victims, average age, and high rate of alcohol intoxication at the time of the incident in this review corresponded with other studies 9,10 . Koh et al 10 reviewed Japanese fatalities or severe injuries to recumbent pedestrians, and similarly demonstrated that these incidents mostly occur during night time, with the most frequent type of vehicle a passenger car.…”
Section: Discussionsupporting
confidence: 84%
“…The male preponderance of victims, average age, and high rate of alcohol intoxication at the time of the incident in this review corresponded with other studies 9,10 . Koh et al 10 reviewed Japanese fatalities or severe injuries to recumbent pedestrians, and similarly demonstrated that these incidents mostly occur during night time, with the most frequent type of vehicle a passenger car.…”
Section: Discussionsupporting
confidence: 84%
“…In this context, such collisions would occur more frequently in rural areas. Concomitant with the study by Tiemensma and Byard, 1 we emphasized the importance of preventing fatalities after collisions between vehicles and pedestrians lying on the road 2,3 …”
mentioning
confidence: 99%
“…In Japan, among all collisions between vehicles and recumbent pedestrians from 2012 to 2018, fatalities accounted for 797 cases, severe injuries needing 30 or more days' treatment for 784 cases, and mild injuries for 871 cases 3 . Therefore, as in Australia, significant numbers of nonfatal collisions between vehicles and recumbent pedestrians have been documented.…”
mentioning
confidence: 99%
See 2 more Smart Citations